Family Business, Cash Holdings, Business Complexity, and Firm Value of Companies Listed in Market Alternative Investment (MAI), Thailand - Thammarong, Monrudee; Petchchedchoo, Pattanant; Kumsuprom, Siridech; Panmanee, Panarat (Rajapark Journal, 2024)
This research aims to 1) study and analyze the relationship between the shareholding structure of family companies, 2) study and analyze the relationship between cash holdings, and 3) study and analyze the relationship between business complexity and business value. The study is quantitative research; the sample group used in this research is 170 companies listed on the MAI Stock Exchange. The statistics used to analyze this research are multiple regression analyses. The results of the research found that 1) the shareholding structure of family companies is related to the value of the business in the same direction, and the market value of common stock prices is related to the value of the business in the same direction. The proportion of ownership and chairman of the board of a family company is not related to the value of the business. 2) Cash holdings are related to the value of the business in the same direction. 3) the number of branches and the number of subsidiaries. Location of subsidiaries in the country Location of overseas subsidiaries and the number of types of businesses operating, there is no relationship with the business value of companies listed on the MAI Stock Exchange.